Existence of infinitely solutions for a modified nonlinear Schrödinger equation via dual approach - Zhang, Xinguang; Liu, Lishan; Wu, Yong Hong; Cui, Y. (Texas State University, 2018)
© 2018 Texas State University. In this article, we focus on the existence of infinitely many weak solutions for the modified nonlinear Schrödinger equation (Formula Presented.) where 1 = a < 2, f ? C(RN× R, R). By using a symmetric mountain pass theorem and dual approach, we prove that the above equation has infinitely many high energy solutions.